Historia Mundo contemporáneo. Siglos XVIII, XIX y XX, Atlas histórico y proyectos de trabajo - FRADKIN, Raúl Coord. (ESTRADA, 1999)
CONTENIDO : COLABORADORES BARRAL, María Elena; BLASCO, María Elida; BURUCUA, José Emilio; CHIARAMONTE, José Carlos; ROMERO, Luis Alberto